PENGARUH MOTIVASI TERHADAP KEDISIPLINAN SISWA DALAM MEMATUHI TATA TERTIB SEKOLAH DI SEKOLAH MENENGAH ATAS (SMA) AL ISLAM 1 SURAKARTA - Nur Kurniawati, Aprilia, Winarno; Rejekiningsih, Triana (Prodi PPKn FKIP UNS, 2017)
ABSTRACTThe objective of research was to find answer to the problem ?Is there an effect of motivation on students? discipline in complying with the school?s rule in High School(SMA) Al Islam 1 Surakarta?. Data analysis was conducted using quantitative approach with correlational research method. The population of research was all of the 10th graders in all majors of SMA Al Islam 1 Surakarta, consisting 341 students. The sample consisted of 172 students taken from all of the 10th grades. The sampling technique used was cluster random sampling and proportional sampling. Data collection was conducted using closed-ended questionnaire technique for data of motivation and students? discipline in complying with the school?s rule. The technique of analyzing data used in this research was correlational analysis using independent and linearity tests, continued with simple linear regression test at significance level of 0.05. Considering the result of research, it could be concluded that ?There is a significant effect of motivation on students? discipline in complying with the school?s rule in SMA Al Islam 1 Surakarta? with tstatistik> ttable or 0.61 > 0.147 at significance level of 5%. The result of coefficient significance test shows tstatistik> ttable or 12.67 > 1.645 at significance level of 5%; therefore, it could be concluded that motivation was correlated significantly to the students? discipline in complying with the school?s rule. Thus, alternative hypothesis (Ha) was supported and null hypothesis (Ho) was not supported. Meanwhile, the size of contribution was 37.21%. It means that 37.21% of students? discipline in complying with the school?s rule was affected by motivation. Keywords: motivation, discipline, compliance, rule